UPACARA ADAT MAPAG PENGANTEN : (Kajian Keislaman dalam Inovasi Tari Lengser Lingkung Seni Siswa SMKN 1 Cikedung Indramayu) - Irmawati Irmawati (Khulasah : Islamic Studies Journal, 2022)
Abstract This research is Fetch of Bride Traditional Ceremony (Islamic Studies in Lengser Dance Innovation by Student Art Group of SMKN 1 Cikedung), intend to describe Islamic studies and innovations contained in the Lengser dance offerings at SMKN 1 Cikedung. This research used a descriptive analysis method with a qualitative approach. Data collection techniques using: direct observation, interviews, literature studies, and documentation. time and place of research are located in the village of Cikedung Lor on Sunday 20 March 2022 at the wedding ceremony of Mrs. Wiwin Suciatin and Mr. Andre Yulian. The findings of the research show that: There is an innovation in the offering of the Fetch of Bride Ceremony by the Students Art Group of SMKN 1 Cikedung a comedic performance of Ki Lengser and Ambu. Besides that, the next innovation is the Mimi Rasinah Kelana Mask Dance at the procession to welcome the arrival of the groom to the bride's residence. As for Islamic studies in offerings Fetch of Bride Traditional Ceremony by the Students Art Group of SMKN 1 Cikedung contained in the contents of the opening of the Rajah which first asked for forgiveness from the God, and then the use of dancer costumes that are closed and cover the headscarf, and Islamic symbols are hidden in the Kelana Mask Dance.